2016
DOI: 10.1111/btp.12380
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate variability on tree demography in second growth tropical forests: the importance of regional context for predicting successional trajectories

Abstract: Naturally regenerating and restored second growth forests account for over 70% of tropical forest cover and provide key ecosystem services. Understanding climate change impacts on successional trajectories of these ecosystems is critical for developing effective large-scale forest landscape restoration (FLR) programs. Differences in environmental conditions, species composition, dynamics, and landscape context from old growth forests may exacerbate climate impacts on second growth stands. We compile data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 224 publications
(262 reference statements)
0
55
0
1
Order By: Relevance
“…Wind and other disturbances can alter successional pathways in regrowing forests (Anderson-Teixeira et al 2013, Uriarte et al 2016. Variability in disturbance risk should thus be taken into account in spatial planning, management, and carbon accounting in tropical secondgrowth forests where the goal is to promote carbon sequestration.…”
Section: Wind Damage In Old-vs Second-growth Forestmentioning
confidence: 99%
“…Wind and other disturbances can alter successional pathways in regrowing forests (Anderson-Teixeira et al 2013, Uriarte et al 2016. Variability in disturbance risk should thus be taken into account in spatial planning, management, and carbon accounting in tropical secondgrowth forests where the goal is to promote carbon sequestration.…”
Section: Wind Damage In Old-vs Second-growth Forestmentioning
confidence: 99%
“…) and could be important drivers of forest demographics, including tree regeneration (Uriarte et al. ). Quantifying how mean climate trends and shorter‐term variability may jointly influence subalpine tree regeneration is an important research direction (Thompson et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Uriarte et al. ). However, these early successional species tend to have faster growth rates under high‐resource conditions (Grime , Bazzaz and Pickett ), meaning they might be better able to take advantage of increased understory light following drought (Slik ), and thus recover more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…, Uriarte et al. ). However, recent work based on remote sensing analyses of large areas has shown that taller forests may exhibit lower sensitivity in their photosynthetic responses to precipitation variability (F. Giardina, A. G. Konings, M. Uriarte, R. S. Oliveira, and P. Gentine, unpublished manuscript ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation